Alexander Camaro (1901-1992) - Leben und Werk - Krüger, Anna (KIT Scientific Publishing, 2021)
In four detailed and richly illustrated chapters, art historian Anna Krüger examines the life and work of painter Alexander Camaro (1901-1992). The study and the catalog raisonné of the paintings are based on a review of the post-war artist's estate. It illuminates the contexts of origin, describes problematic situations and values, and provides insights into the creative process.